Ti / CNT / CNT-Ce-PbO2 anode and preparation method and application thereof
By preparing TI/SNO2-SB/CNT/CE-PBO2 anode on the titanium plate, using the doping of CNT and CE using CNT and CE to solve the problem of insufficient electrode electrode oxidation and stability in the existing technology, realized it more Efficient PABA removal and electrode life extension.
Patent Information
- Application Number
- CN202411491709.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-24
- Publication Date
- 2025-01-28
AI Technical Summary
In the prior art, when removing PABA pollutants in water, the electrodes have insufficient electrocatalytic oxidation capacity and stability, resulting in low removal efficiency and short electrode life.
By preparing TI/SNO2-SB/CNT/CE-PE-PBO2 anode on the titanium plate, the doping of carbon nanotubes (CNT) and rare earth element CE is used to increase the active area and charge transfer capacity of the electrode.
Improve the electrode electrical catalytic activity and the ability to remove organic pollutants, extend the service life of the electrode, and reduce the charge transfer resistance.
Smart Images

Figure CN119370952A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of photoelectrocatalysis technology, and in particular to a Ti / SnO2-Sb / CNT / CNT-Ce-PbO2 anode for photoelectrocatalysis, a preparation method and an application thereof. Background Art
[0002] In recent years, with the continuous discharge of urban industrial wastewater and landfill leachate, the water environment is facing great challenges. Due to the widespread use of pharmaceutical personal care products (PPcPs), it has been detected in dust in the air, water bodies, and human urine and blood. PPcPs include antibiotics, cosmetics, and sunscreens. Para-aminobenzoic acid (PABA) is a commonly used UV filter in sunscreens. With the production and consumption of PPcPs, a large amount of PABA is brought into the water environment, causing certain pollution to the water body. PABA in the water environment is harmful to aquatic organisms and human health. Therefore, an effective method is needed to remove PABA.
[0003] Advanced oxidation technology has a wide range of oxidation characteristics and is a viable removal method. Electrochemical catalytic oxidation and activated persulfate are advanced oxidation technologies for the removal of refractory pollutants. A large number of different studies have shown that the combination of different advanced oxidation technologies can improve the removal efficiency of organic pollutants. In this study, PABA was removed by activated persulfate by modifying the anode and improving the electrocatalytic oxidation ability. Titanium-based PbO2 electrodes have been widely used in wastewater treatment due to their excellent conductivity, excellent catalytic performance and excellent corrosion resistance. The method has disadvantages such as short service life, low current efficiency and electrode detachment, which limit its application in wastewater treatment. In order to improve the electrocatalytic oxidation ability and stability of the electrode, the researchers adopted the modification of the electrode.
[0004] The unique physical properties of carbon nanotubes (CNTs) have attracted great attention, making them a highly valued semiconductor material in the field of scientific research. Carbon nanotubes have a very high specific surface area, which enables the modified electrode to increase active sites, enhance its electrocatalytic oxidation ability, and promote the effective removal of organic matter. The main idea of existing research is to incorporate carbon nanotubes into the active layer to enhance the electrocatalytic activity and stability of the PbO2 electrode. However, modifying the electrode only in the active layer cannot significantly improve the electrocatalytic activity and stability of the electrode. Summary of the invention
[0005] The purpose of the present invention is to provide a Ti / CNT / CNT-Ce-PbO2 anode for photoelectrocatalysis and a preparation method and application thereof. The successful doping of carbon nanotubes and Ce elements is conducive to the increase of the active area of the electrode surface and the enhancement of the charge transfer ability, thereby improving the electrocatalytic activity of the electrode and the removal ability of organic pollutants.
[0006] The technical solution of the present invention:
[0007] A Ti / CNT / CNT-Ce-PbO2 anode comprises, from inside to outside, a titanium plate, a SnO2-Sb base layer, a CNT-α-PbO2 intermediate layer and a CNT-Ce-β-PbO2 active layer.
[0008] A method for preparing a Ti / CNT / CNT-Ce-PbO2 anode, the specific steps are as follows:
[0009] (1) Grinding, surface cleaning and etching of titanium plates;
[0010] (2) uniformly dropping the SnO2-Sb solution onto the titanium plate, and preparing the SnO2-Sb base layer by a thermal deposition method;
[0011] (3) immersing the SnO2-Sb electrode into an alkaline electroplating solution containing PbO, NaOH and CNTs for electrodeposition to prepare a CNT-α-PbO2 intermediate layer;
[0012] (4) The prepared CNT-α-PbO2 intermediate layer was immersed in an acidic electroplating solution containing Pb(NO3)2, HNO3, NaF, CNT and Ce(NO3)3·6H2O for electrodeposition to obtain the Ti / SnO2-Sb / CNT / CNT-Ce-PbO2 anode.
[0013] Beneficial effects of the present invention:
[0014] 1. The present invention successfully modified the PbO2 electrode by doping with rare earth elements Ce and CNT. The surface of the modified electrode is more porous and the particle size is smaller than that of the PbO2 electrode. XPS shows that the Ti / SnO2-Sb / CNT / CNT-Ce-PbO2 electrode has a high O ads Electrochemical characterization showed that the doping of carbon nanotubes and rare earth elements increased the oxygen evolution potential and active surface area of the anode and reduced the charge transfer resistance Rct.
[0015] 2. The present invention successfully modifies the α intermediate layer by adding carbon nanotubes to the electroplating solution of the intermediate layer, and modifies the β active layer of the electrode by adding carbon nanotubes and rare earth element Ce to the electroplating solution of the active layer, thereby constructing a Ti / SnO2-Sb / CNT / CNT-Ce-PbO2 anode. The successful doping of carbon nanotubes and Ce elements is conducive to the increase of the active area of the electrode surface and the enhancement of the charge transfer ability, thereby improving the electrocatalytic activity of the electrode and the removal ability of organic pollutants. BRIEF DESCRIPTION OF THE DRAWINGS
[0016] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments will be briefly introduced below. Obviously, the drawings described below are only embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on the provided drawings without paying creative work.
[0017] Figure 1 SEM images of the PbO2 electrode of Comparative Example 1, the Ti / SnO2-Sb / CNT / CNT-PbO2 electrode of Comparative Example 2, and the Ti / SnO2-Sb / CNT / CNT-Ce-PbO2 of Example 1.
[0018] Figure 2 These are the XRD spectra of the PbO2 electrode of Comparative Example 1, the Ti / SnO2-Sb / CNT / CNT-PbO2 electrode of Comparative Example 2, and the Ti / SnO2-Sb / CNT / CNT-Ce-PbO2 of Example 1.
[0019] Figure 3 XPS spectra of the PbO2 electrode of Comparative Example 1, the Ti / SnO2-Sb / CNT / CNT-PbO2 electrode of Comparative Example 2, and the Ti / SnO2-Sb / CNT / CNT-Ce-PbO2 of Example 1. (a) O 1s spectrum; (b) Ce 3d spectrum.
[0020] Figure 4 Linear sweep voltammetry (LSV) spectra of the PbO2 electrode of comparative example 1, the Ti / SnO2-Sb / CNT / CNT-PbO2 electrode of comparative example 2, and the Ti / SnO2-Sb / CNT / CNT-Ce-PbO2 of example 1.
[0021] Figure 5 Cyclic voltammetry (CV) spectra of the PbO2 electrode of comparative example 1, the Ti / SnO2-Sb / CNT / CNT-PbO2 electrode of comparative example 2, and the Ti / SnO2-Sb / CNT / CNT-Ce-PbO2 of example 1.
[0022] Figure 6 Electrochemical impedance spectroscopy (EIS) spectra of the PbO2 electrode of Comparative Example 1, the Ti / SnO2-Sb / CNT / CNT-PbO2 electrode of Comparative Example 2, and the Ti / SnO2-Sb / CNT / CNT-Ce-PbO2 of Example 1. DETAILED DESCRIPTION
[0023] In order to solve the problems in the background technology, the present invention has invented a Ti / CNT / CNT-Ce-PbO2 anode for photoelectrocatalysis and a preparation method and application thereof, wherein the titanium plate is polished, etched and the surface is cleaned; a SnO2-Sb base layer is prepared on the treated titanium plate by a thermal deposition method, and then a CNT-α-PbO2 intermediate layer and a CNT-Ce-β-PbO2 active layer are prepared by an electrodeposition method. The electrode prepared by the present invention has high electrochemical oxidation performance and can be used in the field of water decomposition photoelectrochemistry.
[0024] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0025] The following examples further illustrate the present invention in detail; however, the protection scope of the claims of the present invention is not limited by the examples.
[0026] Embodiment 1:
[0027] A Ti / CNT / CNT-Ce-PbO2 anode (i.e., a Ti / SnO2-Sb / CNT / CNT-Ce-PbO2 anode) comprises, from inside to outside, a titanium plate, a SnO2-Sb base layer, a CNT-α-PbO2 intermediate layer, and a CNT-Ce-β-PbO2 active layer.
[0028] Preparation of Ti / CNT / CNT-Ce-PbO2 anode (i.e. Ti / SnO2-Sb / CNT / CNT-Ce-PbO2 anode)
[0029] Step 1: The titanium plate was repeatedly polished using sandpaper of different roughness (120, 240, 400 and 600 grit) to remove the oxide layer on the surface of the titanium plate. Subsequently, the titanium plate was continuously ultrasonically rinsed with acetone, ethanol and distilled water for 15 minutes each time. After this step, the polished titanium sheet was etched with oxalic acid (20%) at 100°C for 4 hours until a rough interface was obtained. Finally, they were stored in a solution containing 1% oxalic acid.
[0030] Step 2: The SnO2-Sb base layer was prepared by thermal deposition. The SnO2-Sb solution consisted of 100g SnCl4, 10g SbCl3, 66mL concentrated hydrochloric acid and 200mL isopropanol, which was fixed in a 500mL volumetric flask with isopropanol for dissolution. It is worth noting that the solution is completely anhydrous. Subsequently, the previously stored electrode sheet was taken out and rinsed with deionized water to eliminate the oxalic acid solution remaining on its surface. The SnO2-Sb solution was evenly applied to the surface of the electrode and dried at a temperature of 120°C for 10 minutes. After this step, it was heat treated in a muffle furnace at 550°C for 10 minutes. The whole process was repeated for about 10 to 12 cycles, and the last cycle lasted for 1 hour in the muffle furnace.
[0031] Step 3: Preparation of the intermediate layer: The thermally deposited electrode was immersed in 100 mL of electroplating solution containing 0.1 M PbO, 3.5 M NaOH and 1 g / L CNTs. Electrodeposition was performed at a current density of 5 mA / cm 2 , the temperature is 50°C and the duration is 60 minutes.
[0032] Step 4: Preparation of the active layer: Immerse the prepared intermediate layer in 100 ml of an acidic electroplating solution containing 0.5 mol / L Pb(NO3)2, 1 mol / L HNO3, 0.5 mol NaF, 2 g / L CNT and 10 mmol / L Ce(NO3)3·6H2O. The electrodeposition process was carried out at a current density of 15 mA / cm 2 , the temperature was 65°C, and the time was 60 minutes. After completing the above steps, the Ti / SnO2-Sb / CNT / CNT-Ce-PbO2 electrode was successfully prepared.
[0033] Comparative Example 1: Preparation of pure PbO2 electrode
[0034] The preparation of pure PbO2 electrode can be done by omitting the steps of adding CNT and Ce(NO3)3·6H2O when preparing the intermediate layer and active layer.
[0035] Comparative Example 2: Preparation of Ti / SnO2-Sb / CNT / CNT-PbO2 Electrode
[0036] The preparation of Ti / SnO2-Sb / CNT / CNT-PbO2 electrode can be done by omitting the step of adding Ce(NO3)3·6H2O when preparing the active layer.
[0037] 1. Material Characterization
[0038] Figure 1 The planar SEM images of the electrodes prepared in the comparative example and embodiment 1 are shown in FIG. Figure 1The results show that the surfaces of the three electrodes all present a pyramid structure, but the Ti / SnO2-Sb / CNT / CNT-Ce-PbO2 electrode in Example 1 has a higher particle density and a smaller particle size.
[0039] Figure 2 The XRD spectra of the electrodes prepared in the comparative example and embodiment 1 are shown in FIG. Figure 2 The results show that the diffraction peaks of the three electrodes are similar, such as Figure 2 As shown. In addition, these diffraction peaks closely match those of the β-PbO2 standard card (PDF#76-0564), confirming their accurate identification. Specifically, the XRD spectrum has obvious peaks at 2θ values of 25.4°, 31.9°, 36.2°, 49.1°, 52.1°, 62.5°, and 74.4°, corresponding to the crystal planes (110), (101), (220), (211), (220), (301), and (321). It can be seen from the figure that the intensity of the diffraction peak of the β phase (211) plane is significantly enhanced after the Ce element and carbon nanotubes are doped. This observation indicates that the incorporation of carbon nanotubes and Ce into PbO2 films can promote the selective growth of specific crystal planes. Due to the low content of CNT and Ce in the β-PbO2 film compared to the XRD detection line, the diffraction peaks corresponding to CNT and Ce were not detected.
[0040] Figure 3 The XPS spectra of the electrodes prepared in the comparative example and embodiment 1 are shown in FIG. Figure 3 The results show that Figure 3 a shows that with the increase of binding energy, the characteristic peaks of oxygen (O) at about 529 and 531 eV correspond to the lattice oxygen (O lat ) and adsorbed oxygen (O ads ). Figure 3 The spectrum in b represents the 3d state of Ce, with 6 different peaks, which can be attributed to two different states of Ce, namely 3d 5 / 2 and 3D 3 / 2 It is noteworthy that there is an energy difference of 18.3 eV between these two states, which indicates the successful incorporation of Ce dopant.
[0041] 2. Characterization of electrochemical performance
[0042] In a three-electrode system, an electrochemical station (CHI 660E, Shanghai Chenhua) was used to perform the electrochemical performance test. The specific method is: using the electrode samples prepared in the comparative example and Example 1 as the working electrode, the platinum sheet electrode as the counter electrode, the saturated calomel electrode as the reference electrode, and 0.5M Na2SO4 solution as the electrolyte to perform the electrochemical performance test.
[0043] Figure 4is the linear sweep voltammetric curve of the electrode prepared for the comparative example and Example 1. Figure 4 The results show that the electrode prepared in Example 1 has a higher oxygen evolution potential. It is well known that in the electrochemical oxidation process, a higher oxygen evolution potential corresponds to fewer side reactions and enables the active substances in the system to better attack organic pollutants; therefore, it reflects that the oxidation capacity of the electrode modified by doping CNT and rare earth element Ce is improved.
[0044] Figure 5 The cyclic voltammetry curves obtained at different scan rates for the electrodes prepared in the comparative example and in Example 1 are shown in FIG. Figure 5 The results show that Ti / SnO2-Sb / CNT / CNT-Ce-PbO2 has a larger electrochemically active surface area.
[0045] Figure 6 It is the electrode impedance spectrum prepared for comparative example and embodiment 1. As shown in the figure, the capacitive reactance arcs of the three electrodes are regular semicircles, indicating that their reactions are similar. The electrocatalytic activity of the electrode is related to the radius of curvature observed in the EIS graph. The smaller the radius of curvature, the better the electrocatalytic performance. As can be seen from the figure, compared with the other two electrodes, the radius of curvature of the Ti / SnO2-Sb / CNT / CNT-Ce-PbO2 electrode is smaller, indicating that it has the potential to enhance electrocatalytic ability. Generally, the diameter of the semicircle in the EIS graph represents the charge transfer resistance (Rct). Therefore, the smaller the diameter, the lower the Rct, and the smaller the reaction resistance. Compared with the PbO2 electrode and the Ti / SnO2-Sb / CNT / CNT-PbO2 electrode, the Ti / SnO2-Sb / CNT / CNT-Ce-PbO2 electrode has better charge transfer ability and electrocatalytic oxidation performance.
[0046] Although the present invention is described above through specific embodiments, it should be understood that any equivalent changes made by ordinary technicians in this field without departing from the scope of the present invention should be covered by the protection scope of the present invention.
Claims
1. A Ti / CNT / CNT-Ce-PbO2 anode, characterized in that: From inside to outside, there are titanium plate, SnO2-Sb base layer, CNT-α-PbO2 intermediate layer and CNT-Ce-β-PbO2 active layer.
2. A method for preparing a Ti / CNT / CNT-Ce-PbO2 anode, characterized in that: The specific steps are as follows: (1) Grinding, surface cleaning and etching of titanium plates; (2) uniformly dropping the SnO2-Sb solution onto the titanium plate of step (1), and preparing the SnO2-Sb base layer by a thermal deposition method; (3) immersing the SnO2-Sb electrode of step (2) into an alkaline electroplating solution containing PbO, NaOH and CNTs to perform electrodeposition to prepare a CNT-α-PbO2 intermediate layer; (4) Immerse the CNT-α-PbO2 intermediate layer prepared in step (3) in an acidic electroplating solution containing Pb(NO3)2, HNO3, NaF, CNT and Ce(NO3)3·6H2O for electrodeposition to obtain a Ti / CNT / CNT-Ce-PbO2 anode.
3. The method for preparing a Ti / CNT / CNT-Ce-PbO2 anode according to claim 1, characterized in that: In step (1), the polishing step is to repeatedly polish the titanium plate using sandpaper of 120, 240, 400 and 600 grits in sequence; The cleaning step uses acetone, ethanol and distilled water to continuously ultrasonically rinse and polish the titanium plate, each time for 15 minutes; The etching step is to etch the polished and cleaned titanium sheet with 20% oxalic acid at a temperature of 100° C. for 4 hours until a rough interface is obtained, and store it in a solution containing 1% oxalic acid for later use.
4. The method for preparing a Ti / CNT / CNT-Ce-PbO2 anode according to claim 1, characterized in that: In step (2), the SnO2-Sb solution is composed of 100g SnCl4, 10g SbCl3, 66mL concentrated hydrochloric acid and 200mL isopropanol, and is fixed in a 500mL volumetric flask with isopropanol; The thermal deposition is to drop the SnO2-Sb solution evenly onto the surface of the titanium plate electrode, dry it at 120°C for 10 minutes, and then place it in a muffle furnace at 550°C for 10 minutes, repeat 10-12 times, and the last round lasts for 1 hour in the muffle furnace.
5. The method for preparing a Ti / CNT / CNT-Ce-PbO2 anode according to claim 1, characterized in that: In step (3), during the electrodeposition, the anode is a working electrode and the cathode is stainless steel; The electroplating solution contains 0.1M PbO, 3.5M NaOH and 1g / L CNTs; The current density during the electrodeposition process was 5 mA / cm 2 , temperature is 50℃ and duration is 60 minutes.
6. The method for preparing a Ti / CNT / CNT-Ce-PbO2 anode according to claim 1, characterized in that: In step (4), during the electrodeposition, the anode is a working electrode and the cathode is stainless steel; The electroplating solution contains 0.5 mol / L Pb(NO3)2, 1 mol / L HNO3, 0.5 mol NaF, 2 g / L CNT and 10 mmol / L Ce(NO3)3·6H2O; The current density during the electrodeposition process was 15 mA / cm 2 , temperature is 65℃, time is 60 minutes.
7. Use of the Ti / CNT / CNT-Ce-PbO2 anode according to any one of claims 1 to 6, characterized in that: It is used for photoelectrocatalytic water splitting.